Employee Usage of Mobile Devices Within South African Municipalities, Implications on Policy and Employee Training - Otto, Patrick Margo Margo; Dubihlela, Job; Benedict, Olumide Henrie (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This paper focuses on the importance of policies, procedures and employee training and awareness as aid to manage risks associated with the usage of mobile devices in local government entities in the Namakwa District of the Northern Cape region. A quantitative research method was applied in the study by obtaining responses from a sample of participants in the Namakwa District of the Northern Cape region, using closed-ended questions in the questionnaire, which provided the participants with a predetermined list of coded responses. The results were analyzed and indicated that the majority of the respondents do utilize mobile devices in their organizations. In general, these entities make more use of laptops than any other types of mobile devices. The results indicate that these organizations also still apply the traditional approach of providing their employees with specifically approved types of mobile devices (corporate-owned device) and therefore, do not support the Bring-Your-Own-Device or Choose-Your-Own-Device strategy. There is a clear indication that more efforts are required to ensure improvement, specifically relating to the development of a privacy and security policy and/or procedures as well as providing user training and awareness within municipal organizations.